Mastery Of Online Learning Techniques by Teachers During The Covid-19 Pandemic - metafitri; Sri Handayani Hanum; Ika Pasca Himawati (Talenta Publisher, 2022)
The Covid-19 pandemic has changed many settings, one of which is in the educational process. Through the Circular Letter of the Ministry of Education and Culture Number 4 of 2020, the learning process is carried out with an online learning model. This study aims to describe the implementation of online learning and mastery of online learning techniques by teachers during the Covid-19 pandemic, which previously SMAN 02 Bengkulu City had not implemented online learning but was a cyber school that should have been implemented for a long time. This research uses a qualitative descriptive approach, with data collection techniques through interviews, observations, and documentation. The results of the study were analyzed using functional structural theory proposed by Talcott Persons. The determination of informants was carried out using purposive sampling techniques. The research produced information that the implementation of online learning was carried out using whatsapp groups, google classroom, and several other social media such as Instagram, YouTube. Learning methods from teachers such as making videos, presentations via zoom, and collecting writing assignments through whatsapp groups. Mastery of online learning techniques for teachers does not experience much difficulty because teachers only follow in accordance with learning policies during the Covid-19 pandemic, besides that teachers at SMAN 02 Bengkulu City have high motivation or willingness to face challenges during the Covid-19 pandemic.